4,4’-Bipyridinium 1,1,2,3,3-pentacyanopropenide — new convenient building block for the crystal engineering - Poltorak, D.V.; Gutov, A.V.; Rusanov, E.B.; Chernega, A.N. (Украинский химический журнал, 2009)
The successful combination of the known tectones — 4,4’-bipyridinium cation and 1,1,2,3,3-pentacyanopropenide anion — demonstrate a promising for study and modifications crystal structure with four strong intermolecular interactions of different types and directions (three orthogonal), namely: resonance-stabilized H-bonds, aromatic π-stacking, π-stacking of acyclic systems, and Coulomb attraction amplified by multiple C–H...N contacts; furthermore, there are four groups of chemically equivalent H-bonds directed along the same axis and two different anion geometries in seemingly equal environments. Crystal data: a=9.767(4), b=13.465(8), c=14.274(7) Å, α=97.67(4)⁰, β=107.89(3)⁰, γ=108.19(4)⁰, V=1642(2) Å³, space group P 1 (N 2).